The value of local dexmedetomidine as an adjuvant to ultrasound-guided wide awake local anesthesia no tourniquet (WALANT) in flexor tendon repair surgeries: a randomized controlled trial - Mahmoud Mohammed Alseoudy; Elsayed Mohamed Abdelkarime; Khaled Nour; May Elsherbiny Badr (BMC Anesthesiology, 2024)
Abstract Background The Wide-Awake Local Anesthesia No Tourniquet (WALANT) technique allows intraoperative motor assessment of tendon repair integrity of the hand compared with general anesthesia or brachial plexus block. No studies have tested the effect of adding dexmedetomidine to lidocaine on the analgesic properties of the WALANT technique, which is the aim of our study. Methods A total of 128 patients aged more than 18 years were scheduled for surgical flexor tendon injury repair using WALANT technique. Patients were divided into two equal groups. Ultrasound-guided subcutaneous injection of lidocaine 1% with dexmedetomidine (1 µg/kg), Group D, or without dexmedetomidine, Group C, was performed at four points: proximal to the wrist joint, the distal forearm, palm region, and proximal phalanges. The primary outcome was total morphine consumption throughout the first postoperative day. Secondary outcomes included number of patients requiring rescue analgesia, time to first analgesic request, and pain score. Results Total morphine consumption was significantly (P < 0.001) lower in group D (2.66 ± 0.998) than in group C (3.66 ± 1.144) mg. Number of patients requiring rescue analgesia was significantly (P < 0.001) lower in group D (54.7% (35)) than group C (100.0% (64)). The time for first request for analgesia was significantly (P < 0.001) longer in group D (11.31 ± 6.944) than in group C (5.91 ± 4.839) h. Pain score was significantly higher in group C than D at three (P < 0.001), and six (P = 0.001) hours (P = 0.001) postoperatively. Conclusion Dexmedetomidine significantly improves the analgesic quality of WALANT when added to lidocaine with less opioid consumption. Trial registration (ID: PACTR202203906027106; Date: 31/07/2023).